Smokers' Perspectives on Texting for Tobacco Dependence Treatment: A Qualitative Analysis. Issue 3 (3rd August 2016) - Grau, Lauretta E.; Pham, Timothy; O'Leary, Teresa; Weiss, June; Toll, Benjamin; Bernstein, Steven L.
Abstract: Background: Numerous evidence-based pharmacologic and behavioral approaches exist for the treatment of tobacco dependence. Short-message service texting is a newer modality which shows promise, but smokers' perspectives on texting have not been widely explored. Objective: To use a qualitative research approach to elicit from a sub-sample of participants in a pilot clinical trial their perspectives concerning the feasibility, acceptability, and personal relevance of a publicly available texting program for smoking cessation. Methods: Adult smokers enrolled in the intervention arm in a randomized trial of tobacco treatment were interviewed by telephone. Consenting subjects engaged in a 15–30min semi-structured interview with a trained research assistant, discussing their experience with and attitudes about the texting program and how it affected their tobacco use. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically. Descriptive statistics were calculated for the 16 Likert-formatted items. Results: Of 30 subjects in the intervention arm, 25 (83%) agreed to participate in the qualitative interviews. In general subjects found the program helpful. Common themes were that the texts served as a form of social support, provided useful strategies to reduce tobacco use, validated subjects' attempts to quit, and offered welcome distractions from cravings. Subjects were satisfied with the frequency, timing, and number of texts, although some improvements were suggested. Conclusions: Texting was perceived as feasible, acceptable, and helpful in smokers' attempts to abstain from tobacco. Implications: The major themes identified included the program being a valued source of external support that provided useful strategies to reduce tobacco use. Subjects were satisfied with the frequency, timing, and number of texts. Texting was perceived as feasible, acceptable, and helpful in smokers' attempts to abstain from tobacco. Suggestions to improve the program primarily concerned increasing customizable options and using simple, declarative sentences.